Multi-machine power system stability improvement using an observer-based nonlinear controller - Leon, Enrique Andres (2012)
Control and operation of electric networks undergo several changes due to growing energy coming from renewable sources and demanding power quality standards. New dynamic load features also pose a challenge to grid designers. In addition, economic reasons, an increasing demand and remote generation push transmission lines to their stability limits causing oscillation modes to become more lightly damped. In this context, controllers and devices are used to enhance the performance of the new power systems. In this work, an observer-based controller to improve stability in power systems, by using the excitation of synchronous generators, is introduced. The strategy goal is to attain maximum damping injection and to increase the transient stability, while good voltage regulation performance is maintained. The proposed strategy presents two important features from the implementation point of view. First, the controller only needs sensing currents and rotor speed, and second, previous knowledge of network parameters and topology is not required. Several comparisons in multi-machine scenarios with current power system stabilizers are presented. These studies confirm the viability and the performance improvement when conventional solutions are replaced by the proposed approach.